High incidence of MBL-mediated imipenem resistance among Pseudomonas aeruginosa from surgical site infections in Egypt - Marian R Raouf; Mohamed Sayed; Hazim A Rizk; Noha Anwar Hassuna (Journal of Infection in Developing Countries)
Introduction: Surgical wound infection is a serious problem, especially with metallo-beta lactamases (MBLs)- producing gram-negative bacteria as Pseudomonas aeruginosa. The main objective of this work was to evaluate for the first time in Minia- Upper Egypt, the incidence of imipenem-resistant Pseudomonas aeruginosa infection of surgical wounds particularly that mediated by MBL production.